A quantitative analysis of tumour characteristics in breast cancer patients with extranodal extension in non-sentinel nodes. (April 2018) - O'Keeffe, N.A.; O'Neill, C.; Zahere, A.; Livingstone, V.; Browne, T.J.; Redmond, H.P.; Corrigan, M.A.
Abstract: Background: The presence of extranodal extension (ENE) is well documented as a predictor of non-sentinel lymph node (NSLN) metastasis. The ACOSOG Z0011 trial (2011) concluded that patients who satisfy criteria including the absence of sentinel lymph node (SLN) ENE can forgo axillary clearance (AC). Currently there are no studies analysing the rate of ENE in NSLN metastasis in which the sentinel node was positive but had no ENE. Determining this incidence will help determine if current paradigms are resulting in residual ENE in NSLN metastasis by forgoing AC based on the Z0011 trial.. Methods: This study determined incidence of ENE at NSLN metastasis in patients with a positive SLN biopsy without ENE in 162 symptomatic breast cancer patients who underwent AC between 2009 and 2014 at Cork University Hospital Breast Cancer Service, a teaching hospital of University College Cork. Results: Of 965 sentinel node biopsies performed 251 were identified as SLN positive, 162 (64.5%) underwent further AC. Of the 162 patients, 56.8% (92/162) were positive for ENE at SLN, of these 57.6% (53/92) had NSLN metastasis versus 17.1% (12/70) in the ENE-negative group (χ 2 test; P  < 0.001). On adjusted analysis, ENE at the SLN was a significant predictor of NSLN metastasis (odds ratio [OR] 8.63; 95% confidence interval [CI] 3.26–22.86; P  < 0.001). The incidence of NSLN-ENE in patients without SLN-ENE was 1/70 (1.4%) compared with 33.7% (31/92) in patients who had ENE at the SLN (χ 2 test; P  < 0.001). Conclusion: ENE at the SLN is an independent predictor of NSLN involvement; its absence significantly reduces the likelihood of ENE in NSLN metastasis.. Highlights: Extranodal extension is an independent predictor of non-sentinel node involvement. The incidence of ENE at NSLN when absent at the SLN has not been described. The incidence of NSLN-ENE in patients without SLN-ENE was 1.4%. The absence of SLN ENE significantly reduces the likelihood of NSLN ENE.